A new cavernicolous species of the genus Bergrothia Reitter, 1884 (Coleoptera, Staphylinidae, Pselaphinae) from Georgia - Maghradze, Eteri; Faille, Arnaud; Barjadze, Shalva; Hlaváč, Peter (Zootaxa, 2019)
During a biospeleological survey of caves of Imereti region (Georgia), a new species of the beetle genus Bergrothia Reitter, B. barbakadzei sp. nov. was discovered in three caves: Datvis (Bear), Prometheus and Melouri caves (Sataplia–Tskaltubo karst massif, Tskaltubo district). The new species is described, illustrated and differentiated from other morphologically similar species of the genus—B. mingrelica (Reitter). Bergrothia barbakadzei sp. nov. is the first cavernicolous species of the genus Bergrothia. A key to the species of this genus is provided.